Political pressures and hesitations, Portugal, the United States of America and the operation Nickel Grass: Final stages on the way to the end of the Portuguese colonial empire - Rocha, J. S. (The Creation of New States and the Collapse of Old Empires In the XX Century: Acta, 2021)
A Portuguese historian once wrote, "international relations have multiple requirements that can only be thought of on the basis of absolute realism and skilful calculation of currently available forces. Among them is the strategic function of a territory, not only for the state that owns that territory but also the appraisal of the interest it represents for other 'securities'. However, the strategic value of a territory will only adds value to the State that holds it if that State has diplomatic skills and capacities to exploit the conditions of the moment in order to ensure an advantage position." 1